Physical performance on the early 6-minute walk test in coronary artery bypass grafting patients during inpatient cardiac rehabilitation - Wu, Yao; Ren, Bao; Li, Jing; Chi, Liqun; Li, Ping; Wu, Jiahui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe 6 min walk test (6MWT) is widely used to evaluate functional exercise capacity, therapeutic effects, and prognosis in patients with cardiopulmonary diseases. However, its application in phase I cardiac rehabilitation (CR) after coronary artery bypass grafting (CABG) remains under explored. This study investigates the physical performance of CABG patients during the early 6MWT and analyzes factors influencing their walking performance during inpatient CR.MethodsThis retrospective study included 360 patients who underwent isolated off-pump coronary artery bypass (OPCAB, n = 240) or minimally invasive direct coronary artery bypass (MIDCAB, n = 120) surgery. Participants, with a median age of 63 years (range: 36–80), comprised 285 males and 75 females. The study was conducted from November 22, 2023, to December 25, 2024. It specifically included patients who completed the 6MWT within 5 ± 2 days during phase I CR post-surgery.ResultsThe median 6 min walk distance (6MWD) was 183 ± 125 meters (33 ± 20% of predicted). Notably, the walking distances were significantly shorter in OPCAB patients than MIDCAB patients (175 ± 125 vs. 200 ± 134 meters, Z = −3.426, P = 0.001), in older patients than younger patients (H = 20.489, P < 0.001) and in females than males (150 ± 84 vs. 200 ± 100 meters, Z = −5.919, P < 0.001). Univariate analysis showed 6MWD significantly correlated with height, weight, body mass index (BMI), diastolic blood pressure (DBP) and peripheral oxygen saturation (SpO2) before the test, as well as heart rate (HR), systolic blood pressure (SBP), DBP, SpO2, and respiratory rate (RR) after the test, and the mean values of HR and RR during the test. The stepwise multivariate regression analysis identified that gender, type of surgery, HR and RR at the end of the test, and DBP before the test were independent predictors of the 6MWD.ConclusionThis study is the first to describe early 6MWD in CABG patients during phase I CR. The 6MWT is feasible and well-tolerated in adults and older patients shortly after CABG. The findings provide valuable insights into factors affecting walking distance, aiding clinical assessment and informing phase II CR program development post-discharge.